Use of magnetic resonance imaging in the diagnosis of idiopathic inflammatory myopathies - A. N. Khelkovskaya-Sergeeva; L. P. Ananyeva; D. O. Kazakov; E. L. Nasonov (Современная ревматология, 2019)
Idiopathic inflammatory myopathies (IIMs) are a group of autoimmune diseases characterized by cross-striated muscle inflammation accompanied by muscle weakness. The rarity of these diseases and a large number of other diseases with similar clinical presentation, along with the absence of simple laboratory tests for confirming the diagnosis of IIMs can cause diagnostic difficulties. The latter may particularly frequently occur in the differentiation of polymyositis from sporadic inclusion body myositis, and late-onset limb-girdle muscular dystrophies. Magnetic resonance imaging of the thigh and leg muscles is of great importance for the differential diagnosis of myopathies, including autoimmune ones.